A diarsagermylene and a diarsastannylene stabilised by arene⋯Ge/Sn interactions. Issue 20 (20th February 2018) - Izod, Keith; Evans, Peter; Waddell, Paul G.
Abstract : Unusual arene⋯Ge/Sn interactions stabilise the rare diarsatetrylenes8Ge /Sn by up to 181 kJ mol −1 . Abstract : The synthesis and structures of two new diarsatetrylenes {(Dipp)2 As}2 E are presented [E = Ge, Sn; Dipp = 2, 6-diisopropylphenyl]. The high barrier to planarisation of As prevents stabilisation by As–E π-interactions; however, arene⋯Ge/Sn interactions stabilise these compounds by up to 181.4 kJ mol −1 . This represents a new stabilisation mode for this class of compounds.